Making her mark Raton native designs look for buy corner - Ferrendelli, Betta (Raton Range Raton, New Mexico, 1990)
Newspaper Article on Carole Kastler and her new career in landscaping and floral designing, interior plantscaping and consulting. Kastler designed the landscape for the Welcome Center in Raton, New Mexico.
Master list item #: 35
File location is in the Raton File Cabinet
Keywords: Kastler, Carole; Neal, Jeff; Camolot Design; Raton Welcome and Tourist Information Center; Raton Chamber and Economic Development Council; Denver University; University California; Tagawa; Beardsley/Miller Corporation; Local History; Biography; Life and Customs; Career; Landscaping; Floral designing; Interior Plantscaping; Consulting; Education; Raton, New Mexico; Denver, Colorado; Clayton, New Mexico; San Diego, California; Santa Barbara, California